IMPLEMENTATION OF TALKING STICK MODEL IN ECONOMICS TO FOSTER INDEPENDENCE OF GRADE XI STUDENTS AT MA MIFTAHUL ULUM SUREN - Lisa Umami; Arie Eko Cahyono; Shendy Andrie Wijaya (STKIP Persada Khatulistiwa Sintang, 2025)
This study explores the implementation of the Talking Stick learning model in the Economics subject and its role in fostering student character in Grade XI at MA Miftahul Ulum Suren. The research stems from the growing need to integrate character education into classroom learning in a meaningful and contextual manner. Using a qualitative approach and a case study design, data were collected through observation, in-depth interviews, and documentation. The findings reveal that the Talking Stick model encourages active student participation and cultivates key character traits such as responsibility, honesty, self-confidence, cooperation, and discipline. Classroom dynamics showed significant behavioral shifts, especially in students’ willingness to express opinions and take turns respectfully. Supporting documents such as lesson plans, teacher journals, and photos indicate well-structured planning and consistent implementation. The study concludes that the Talking Stick model is not only effective for delivering Economics material but also instrumental in instilling social values and positive behaviors. It is particularly suitable for religious-based schools seeking to strengthen character development alongside academic learning. The study recommends that educators adopt active and participatory models to enhance both instructional quality and moral education.